Cancer of the cervix: a sexually transmitted infection? - Beral, V (1974)
When mortality patterns for cancer of the uterine cervix were compared with trends in incidence of sexually transmitted diseases in both England and Wales and in Scotland, there were striking associations between the temporal, social class, occupational, and geographic distributions of these diseases. The data suggest that exposure to sexually transmitted infection is an important determinant of cervical cancer. Although they are still young, women born after 1940 are already experiencing increased cervical-cancer mortality. If cervical-cancer prevention and therapy remain unchanged, this generation's high risk of death from cervical cancer will probably continue to operate throughout their lives. © 1974.